Spirits of just men : mountaineers, liquor bosses, and lawmen in the moonshine capital of the world - Thompson, Charles D., Jr. (Charles Dillard), 1956- (University of Illinois Press, 2011)
"Spirits of Just Men tells the story of moonshine in 1930s America, as seen through the remarkable location of Franklin County, Virginia, a place that many still refer to as the "moonshine capital of the world." Charles D. Thompson Jr. chronicles the Great Moonshine Conspiracy Trial of 1935, which made national news and exposed the far-reaching and pervasive tendrils of Appalachia's local moonshine economy. Thompson, whose ancestors were involved in the area's moonshine trade and trial as well as local law enforcement, uses the event as a stepping-off point to explore Blue Ridge Mountain culture, economy, and political engagement in the 1930s. Drawing from extensive oral histories and local archival material, he illustrates how the moonshine trade was a rational and savvy choice for struggling farmers and community members during the Great Depression. Local characters come alive through this richly colorful narrative, including the stories of Miss Ora Harrison, a key witness for the defense and an Episcopalian missionary to the region, and Elder Goode Hash, an itinerant Primitive Baptist preacher and juror in a related murder trial. Considering the complex interactions of religion, economics, local history, Appalachian culture, and immigration, Thompson's sensitive analysis examines the people and processes involved in turning a basic agricultural commodity into such a sought-after and essentially American spirit"--